2019
DOI: 10.1007/s40093-019-00315-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of organic amendment on some soil physicochemical characteristics and vegetative properties of Zea mays in wetland soils of the Niger Delta impacted with crude oil

Abstract: Purpose This study sought to investigate the effects of organic amendments on the degradation of hydrocarbons and vegetative properties of Zea mays grown in crude oil-contaminated wetland soils of the Niger Delta, Nigeria. Methods Two soil types were investigated, namely, fadama soil (oxisol) and swamp forest soil (utisol). For each soil type, 48 treatment cells and 1 control containing 1 kg of soil each were spiked with crude oil at concentrations ranging from 50 to 200 g kg −1 , representing 5-20% (m/m) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
1
3
1
2
Order By: Relevance
“…The result revealed that the soil samples can influence corrosion. The study revealed temperature that is consistent with temperature of the region and a usual characteristic of Niger Delta region soil [25]. This is also identical to the report of [26].…”
Section: Results and Discusionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result revealed that the soil samples can influence corrosion. The study revealed temperature that is consistent with temperature of the region and a usual characteristic of Niger Delta region soil [25]. This is also identical to the report of [26].…”
Section: Results and Discusionsupporting
confidence: 90%
“…Highly acidic soils clearly indicate a high corrosion risk to buried facilities. pH combines with the aerobic situations in the soil environment can influence the character of microbial activity that have a huge effect on corrosion rates as revealed by [2,1,25] Therefore, based on the pH values of the soil samples, the soil from these communities may be mildly corrosive towards buried pipeline.…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the continuous pollution of the garage and industrial sites with petroleum fuels could have led to significant increase in the content of both organic matter and these nutrients, as reported elsewhere [ 58 ]. These results are partly in disagreement with the findings of Egobueze,Ayotamuno [ 59 ], who observed that petroleum fuel contamination increased the amount of organic matter but decreased the available phosphorous and nitrogen [ 59 ]. Though some researchers have reported that the high nutrient content of petroleum fuels supports the growth of oil degrading bacteria [ 60 , 61 ], there is evidence that the alterations in soil properties resulting from oil pollution impair plant growth and other ecosystem services [ 62 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Siendo Nigeria el país más representativo con una cantidad de 9 artículos representan el 37.5% del total de artículos seleccionados. Esto se debe a que este país es una zona rica en petróleo altamente poblada y sus ecosistemas han sido impactados gravemente por los efectos del petróleo e hidrocarburos [15], lo que conlleva a la degradación de tierra agrícolas, vegetación y acuicultura [24]. Por otro lado, Brasil, Sudáfrica, Polonia, Egipto, Arabia Saudita y Tailandia representan cada uno el 4.16% ya que solo cuentan con un artículo seleccionado.…”
Section: Scielounclassified